Report of a Rare Case of Ovarian Cyst: Cystadenoma of the Rete Ovarii - Aslıhan Yazıcıoğlu; Özge Senem Yücel; Mert Turğal; Güneş Güner; Özgür Özyüncü; Alp Usubütün; Sinan Beksaç (Medical Network, 2012)
The cystic formation of the rete ovarii has been described rarely in the medical literature. Before performing pathologic examination they are mostly confused with other ovarian cystic structures. Currently, with the help of the certain distinguishing features of the rete ovarii tumors, diagnosing a primary tumor of the rete ovarii is much easier. Herein we describe a case of a postmenopausal patient presenting with a right sided adnexal mass, a rare tumor of t he rete ovarii, the cystadenoma.